Teachers' Attitudes Toward the Use of Technology in Social Studies Teaching - Emin Kilinc; Seray Kilinc; Mehmet Melik Kaya; Enis Harun Başer; Hafize Er Türküresin; Alper Kesten (Research in Social Sciences and Technology, 2016)
Technology integration in education is one of the most popular topics in the last decades. Many countries have invested millions of dollars to equip classrooms with technological devices. As well as developed countries, Turkey has conducted several projects to provide technological devices and educational materials to classrooms. Technology has the potential to increase the quality of learning and teaching process. However, having technological devices in classroom alone will not cause the increase of the quality of education. Thus, the purpose of this study is to examine teachers' attitudes toward the use of technology in social studies teaching. Understanding social studies teachers' attitudes is essential because it is a way to figure out how they integrate technology and define barriers. The authors applied quantitative survey method and used cluster sampling to choose participants. The sample of the study consisted of 155 social studies teachers who are currently teaching at middle schools. The use of technology in social studies teaching attitude scale was used to collect data. The findings revealed that teachers have positive beliefs and attitudes toward the use of technology. Also, the findings showed that teachers who are working at private schools have significantly high attitudes than others who are teaching at public schools. Moreover, teachers who took educational technology and teaching material course and attended in-service training have more positive attitudes than others.